Under the weather : reimagining mobility in the climate crisis - Sodero, Stephanie, 1978- (McGill-Queen's/Brian Mulroney Institute of Government studies in leadership, public policy, and governance ;, 2022)
"Humans and human mobility, including driving and flying, are entangled with the climate emergency. Fossil-fuelled mobility worsens severe weather, and in turn, severe weather disrupts human mobility. A shift to zero-emission vehicles is critical but insufficient to repair the damage or prepare communities for the coming disruptions severe weather will bring. In Under the Weather Stephanie Sodero explores the intersection between human mobility and severe weather. Anchored in two Atlantic Canadian hurricane case studies, Hurricane Juan in Mi'kma'ki/Nova Scotia in 2003 and Hurricane Igor in Ktaqmkuk/Newfoundland in 2010, the book contributes to contemporary cultural and policy discussions by offering five practical recommendations--revolutionize mobility, prioritize vital mobility of medical goods and services, embrace ecological mobilities, rebrand redundancy, and think flexibly--for how mobility can be reimagined to work with, rather than against, the climate in ways that also benefit the health, education, and economy of local communities. This ecological approach to mobilities sheds light on extreme mobility dependency and the impact of mobility disruptions on the ground in Canadian communities. Focusing on the entangled relationship between human mobility and the climate, Under the Weather examines how communities can transform their relationship with mobility to enable greater resilience."--